Game-Based English Learning for Young Learners: A Systematic Review - Alfi Diotama Saputra; Livia Septiani; Rezki Adriani; Hanna Sundari (JEdu: Journal of English Education, 2021)
Games has been extensively known to increase students' motivation and interest in learning English. However, its main findings and the trends in English teaching and learning for young learners are still unknown. To fill the gap, the aim of this study was to examine the application of games-based English learning for young learners. A literature analysis was conducted to several databases including Garuda, Science Direct, Google Scholar, Research Gate, Taylor and Francis, Eric, and Jour. System, and a total of 30 journals were analyzed through systematic review was used as the research methodology. The journals were analyzed utilizing a content analysis method and the data are presented in systematic diagrams and tables. The result of the study revealed that game-based English learning was very popular among Indonesian English young learners between the years 2011-2021. In 2020, the popularity of games based on English learning was very high. In addition, the most used research method in game-based English learning studies was quantitative method. Moreover, game-based English learning was most implemented at the elementary school levels, and the most learned language skill was to increase vocabulary. Further analysis of challenges, advantages and effectiveness related to the use of game-based English learning for young learners was also illustrated.